2016
DOI: 10.1111/imb.12213
|View full text |Cite
|
Sign up to set email alerts
|

Expression and characterization of a recombinant i‐type lysozyme from the harlequin ladybird beetle Harmonia axyridis

Abstract: Lysozymes are enzymes that destroy bacterial cell walls by hydrolysing the polysaccharide component of peptidoglycan. In insects, there are two classes of lysozymes, the c-type with muramidase activity and the i-type whose prototypical members from annelids and molluscs possess both muramidase and isopeptidase activities. Many insect genes encoding c-type and i-type lysozymes have been identified during genome and transcriptome analyses, but only c-type lysozymes have been functionally characterized at the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The lysozyme complexes probably evolved for release through N. vespilloides anal secretions and diversified to produce multiple enzyme variants in this species. The c-type and i-type lysozymes expressed in the N. vespilloides gut could show either digestive or immunity-related functions, the latter by potentiating the activity of other AMPs such as coleoptericins2324. The diversity of AMPs and lysozymes may also protect against rapidly evolving pathogens or unpredictable pathogen diversity in the soil2526.…”
Section: Discussionmentioning
confidence: 99%
“…The lysozyme complexes probably evolved for release through N. vespilloides anal secretions and diversified to produce multiple enzyme variants in this species. The c-type and i-type lysozymes expressed in the N. vespilloides gut could show either digestive or immunity-related functions, the latter by potentiating the activity of other AMPs such as coleoptericins2324. The diversity of AMPs and lysozymes may also protect against rapidly evolving pathogens or unpredictable pathogen diversity in the soil2526.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to playing some role in digestion, lysozymes are antimicrobial proteins that hydrolyse residues of peptidoglycan, which is the predominant cell wall polymer of bacteria (Fukamizo, ). In insects, lysozymes are mainly expressed in the fat body, and after immune challenge also in the hemocytes (Barthel et al., ; Beckert et al., ; Zhang et al., ), but were also shown to play important roles in the gut (Jacobs et al., ; Johnston & Rolff, ). Specific plant compounds of S. alba may act on the insect microbiota of P. cochleariae , thereby affecting immune responses particularly in larvae of the SS line.…”
Section: Discussionmentioning
confidence: 99%
“…The i-type lysozymes have muramidase and isopeptidase activities, but the i-type lysozymes in insects lack muramidase activity. In addition, some i-type lysozymes cannot be induced by immune stimulation, which indicates that they may have acquired new and undetermined functions in the process of evolution [12]. Researchers have suggested that c-type lysozymes are not only involved in immune defense but are also involved in insect digestion.…”
Section: Introductionmentioning
confidence: 99%